2019
DOI: 10.1007/s12144-019-00412-9
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity and rumination mediate the relationship between loneliness and well-being

Abstract: In recent years, plentiful data has emerged indicating the detrimental effects of loneliness on well-being. One of the challenges for researchers dealing with this issue is to find the mechanism underlying the relationship. The present study investigated 293 adults, aged 19-40, and examined whether authenticity and rumination functioned as mediators in the relationship between loneliness and well-being (and its three domainspleasure, engagement, and meaning). The results of the study confirmed the lonelinesswe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 58 publications
5
26
0
1
Order By: Relevance
“…In turn, it is possible that those who are already lonely are predisposed to ruminating about these kinds of concerns. This finding is consistent with past research that has found that increased rumination is associated with greater loneliness (Gan et al, 2015;Borawski, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In turn, it is possible that those who are already lonely are predisposed to ruminating about these kinds of concerns. This finding is consistent with past research that has found that increased rumination is associated with greater loneliness (Gan et al, 2015;Borawski, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Given these observations, fear of not mattering to others may be another correlate of loneliness. Certainly past research has found that rumination is associated with greater loneliness among young adults (Gan et al, 2015;Borawski, 2019).…”
Section: Mattering and Lonelinessmentioning
confidence: 99%
“…The present findings are also in line with earlier research outcomes regarding the association between loneliness and mental health and well-being [31,32]. More specifically, cross-sectional results from the context of current pandemic showed that loneliness is positively associated with negative indicators of mental health and negatively associated with positive indicators of mental health [19,20,33,34].…”
Section: Discussionsupporting
confidence: 92%
“…Our emphasis on this element reflects our sense that physical isolation during the pandemic has resulted in many people having overwhelming feelings of anxiety that may have resulted in a cognitive preoccupation to the point that some people can no longer stand the thought of being lonely for any significant stretch of time. Moreover, from a social science perspective, while there has not been, to our knowledge, any research thus far on lonelinessrelated automatic thoughts, there have been several studies that have linked loneliness with the ruminative brooding that is known to prolong and exacerbate depression (e.g., Borawski 2019;Vanhalst et al 2012;Zawadzki et al 2013). The notion that there is a cognitive element to loneliness that remains to be addressed represents a potentially important extension of the loneliness construct.…”
Section: Facets and Features Of Lonelinessmentioning
confidence: 99%